Is Iconic Memory Iconic? - Quilty‐Dunn, Jake (Philosophy & Phenomenological Research, 2020)
Short‐term memory in vision is typically thought to divide into at least two memory stores: a short, fragile, high‐capacity store known as iconic memory, and a longer, durable, capacity‐limited store known as visual working memory (VWM). This paper argues that iconic memory stores icons, i.e., image‐like perceptual representations. The iconicity of iconic memory has significant consequences for understanding consciousness, nonconceptual content, and the perception–cognition border. Steven Gross and Jonathan Flombaum have recently challenged the division between iconic memory and VWM by arguing against the idea of capacity limits in favor of a flexible resource‐based model of short‐term memory. I argue that, while VWM capacity is probably governed by flexible resources rather than a sharp limit, the two memory stores should still be distinguished by their representational formats. Iconic memory stores icons, while VWM stores discursive (i.e., language‐like) representations. I conclude by arguing that this format‐based distinction between memory stores entails that prominent views about consciousness and the perception–cognition border will likely have to be revised.